Comparative effects of histone deacetylases inhibitors and resveratrol on Trypanosoma cruzi replication, differentiation, infectivity and gene expression - Campo, Vanina Andrea (2017)
Histone post-translational modification, mediated by histone acetyltransferases and deacetylases, is one of the most studied factors affecting gene expression. Recent data showing differential histone acetylation states during the Trypanosoma cruzi cell cycle suggest a role for epigenetics in the control of this process. As a starting point to study the role of histone deacetylases in the control of gene expression and the consequences of their inhibition and activation in the biology of T. cruzi, two inhibitors for different histone deacetylases: trichostatin A for class I/II and sirtinol for class III and the activator resveratrol for class III, were tested on proliferative and infective forms of this parasite. The two inhibitors tested caused histone hyperacetylation whereas resveratrol showed the opposite effect on both parasite forms, indicating that a biologically active in vivo level of these compounds was achieved. Histone deacetylase inhibitors caused life stage-specific effects, increasing trypomastigotes infectivity and blocking metacyclogenesis. Moreover, these inhibitors affected specific transcript levels, with sirtinol causing the most pronounced change. On the other hand, resveratrol showed strong anti-parasitic effects. This compound diminished epimastigotes growth, promoted metacyclogenesis, reduced in vitro infection and blocked differentiation and/or replication of intracellular amastigotes. In conclusion, the data presented here supports the notion that these compounds can modulate T. cruzi gene expression, differentiation, infection and histones deacetylase activity. Furthermore, among the compounds tested in this study, the results point to Resveratrol as promising trypanocidal drug candidate.